Sytuacja finansowa gospodarstw prowadzących rachunkowość rolną w latach 1994-1995 - Bereżnicka, Joanna (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 1997)
The author in this report tried to evaluate the conditions of various sizes farms. In conducting the review, the vertical analysis was based both on the financial statements for given years (assets and liabilities structure analysis) and on specific financial ratios (liquidity ratios, ability to pay ratios, profitability ratios). In addition, factors of production (land, labour and capital) costs were presented. In brief, financial statements analysis methods revealed that, the main position of assets constituted tangible assets, while owner's equity dominated in liabilities. The given liquidity ratios presented satisfactory level, however return on capital ratio should be taken under consideration. The above rate, in the surveyed group of holdings in the given period, was never higher than the interest rate of credits offered by banks. What was found, in brief, is that only larger farms ( 1 O ha and up) were able to cover the labour and capital cost from their income. Smaller farms were able to cover merely 50 per cent of labour wages (at the level of parity equal to 80 per cent). There is evidence to suggest that the main part of income in small farms, was not earned through forming itself. These farms have limited potentials for further growth.